Real-time whiteboard / Ng Yih Young - Ng , Yih Young (2002)
Animated chat room is a system that combines chat application, animation, Text-To - Speech system, and real time activity. This huge system is divided into three major parts which are chat room application and graphical user interface (GUI) design, animation and Text - To - Speech (TTS) design, and real time activity - whiteboard. Mr.Tan Check Learn will in charge in the chat room application, Ms. Tan Su Yuen will cover the animation and TTS design and I myself will involve in the real time activity - whiteboard. The whiteboard system is an enhance feature for the chat room application. Whiteboard allows users at the same session (on-line at the same time) top post object or to draw something for others users to see. Whiteboard share users creativity. Nowadays, although there are a lot of whiteboard system, but this whiteboard will still how the different from them because this system will focus on real time activities and user friendly interface A lot of the research and review had done to complete this system. For instance, Real-time Transport Protocol (RTP), Object - Oriented programming language, methodology, Transmission Control Protocol (TCP), User Datagram Protocol (UDP) and so on. The whiteboard module can be divided into 4 sub modules, these are drawing module, text module, colour module and manipulation module. Each module will focus on different parts of the system.